Eine ländliche Siedlung der römischen Kaiserzeit mit Eisenverhüttung auf der Schleswiger Geest. Der Fundplatz Bollingstedt LA 41 . . - Harten, Lorenz (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
The development of a new housing area on the northern side of the village of Bollingstedt, District of Schleswig-Flensburg, led to the discovery of a settlement from the Roman Iron Age. It was excavated from April to July 2023. More than fifteen structures were discovered in an area of about 2 hectares. Two farmsteads that also included roofed fences indicate settlement continuity over two or three phases. Old longhouses were replaced by new ones on the same spot, indicating a longer period of occupation that dates chiefly to the late 1st century BC to the 4th century AD. 229 bloomeries show the intense exploration of local bog iron ores from the Roman Iron Age onwards. In one house context, hammerscale was discovered, proving the further processing of the sponge iron.